Incidence and Survival Analysis of Gastrointestinal Stromal Tumors in Shanghai: A Population-Based Study from 2001 to 2010. (23rd April 2014) - Lv, Minzhi; Wu, Chunxiao; Zheng, Ying; Zhao, Naiqing
Abstract : Objectives. A population-based study was undertaken to investigate the epidemiological features of gastrointestinal stromal tumors (GISTs) in Shanghai, especially the incidence and the preliminary exploration of survival. Methods. A total of 1923 patients with GISTs diagnosed from 2001 to 2010 in Shanghai were reviewed. The annual incidence and overall survival of GISTs were calculated; Cox proportional hazards' regression was used to analyze several prognostic factors. Results. The average crude incidence of GISTs was 2.11 per 100, 000 between 2004 and 2008, and the age-standardized incidence was 1.28 per 100, 000. The incidence increased gradually from 2004 to 2008. In addition, 57% of cases had GIST in the stomach and 33% in the intestine. The 5-year overall survival of GISTs was 86.98%. The Cox regression analysis showed older age (≥65 yr versus <40 yr, HR = 5.085; (40, 65) yr versus <40 yr, HR = 1.975), male gender (HR = 1.474), and tumor locations (intestinal versus stomach, HR = 1.609) were predictors of its mortality. Conclusion. GISTs, mainly occurring in the stomach, are more common in elderly population, with an increasing incidence from 2004 to 2008. Older age, male gender, and tumor locations are risk factors for its mortality.